Study of mechanical behavior of steel fibre oil palm shell concrete (SF-OPSC) - Nur Irwani, Othman (2015)
Oil Palm Shell (OPS) is one of the waste material that can be innovating as construction material in construction industry to minimize wastage. OPS can be obtained from landfill of Palm oil mill factory. The study on OPS was not new, especially towards its application as a coarse aggregate in concrete containing steel fibre reinforcement. The used of OPS in a concrete can developed a new lightweight concrete. However, there is still lack of published behavior towards such application. Therefore, this study focused on fill the lack of information .The sizes of specimens tested are 100 mm x 100 mm x 100 mm of cube for compression, cylinder with 150 mm diameter and 300 mm height for splitting tensile strength and modulus of elasticity and prism with cross section is 100 mm x100 mm x 500 mm for flexural strength. The results shows that concrete containing OPS gives lower compressive strength compared to control (without OPS). The values werexxxx for control, while 18.67 MPa-24.72 MPa for cubes with 50% OPS and 13.51 MPa – 17.50 MPa for cubes with 100% OPS. In term of speciality tensile strength: cylinder with 50% OPS shows a bit higher compared with control. While, cylinder with 100% OPS gives the lowest strength. On the other hand, inclusion of 50% OPS to the prism increase for 15.70 % and inclusion of 100% OPS increased for 2%, compared to control. Lastly, inclusion of OPS to the cylinder, towards the modulus of elasticity shows no effect to the concrete. In conclusion, inclusion of OPS to the concrete containing steel fibre strongly depends on the type of mechanical behavior (example: either compressive strength, flexural strength, splitting tensile strength or modulus of elasticity).